PEMBELAJARAN BERBASIS MIND MAP UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI RELASI & FUNGSI - Flavia Aurelia Hidajat (Jurnal Pendidikan Edutama, 2017)
Abstract: Mind map-based Learning to Enhance Students’ Learning Outcomes of Relations and Functions Materials. This study is a classroom action research that aims to describe the mind map-based learning that can improve student learning outcomes in relation and functions materials. The subjects were students of class X BKJ 2 SMKN 5 Jember. The results showed that the learning-based mind map that can improve student learning outcomes in the material of relations and functions include two-cycle with four phases: (1) planning to prepare and validate the lesson plan (RPP), student’ worksheet (LKS), observation sheet activities of teachers and students, and the final test cycle, (2) the implementation of action which include: a) the activities of preliminary with deliver of learning objectives, given of motivate, provide an explanation of the use of mind mapping and conduct a question and answer for dig students' initial knowledge about previous material and the material to be learned; b) the activities of core with forming of students in small groups, students are given worksheets, students discuss in small groups, write down the results of the discussion on worksheets, create a mind map related to the discussion results for presentation to the class, and then present it to the class. At the time of presentation occurs asked-questions and discussions in the class related to the result of presentations; c) the activities of cover that is teachers evaluate the results of class discussion and the results of the mind map group that has been presented, (3) the observation made by three observer, (4) the reflection about the results of the test, mind map and observations.Keywords: Mind Map, Learning Outcomes, Relation & Functions         Abstrak: Pembelajaran Berbasis Mind Map Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Relasi dan Fungsi. Penelitian ini merupakan tindakan kelas yang bertujuan untuk mendeskripsikan pembelajaran berbasis mind map yang dapat meningkatkan hasil belajar siswa pada materi relasi & fungsi. Subjek penelitian adalah siswa kelas X BKJ 2 SMKN 5 Jember. Hasil penelitian menunjukkan bahwa pembelajaran berbasis mind map yang dapat meningkatkan hasil belajar siswa pada materi relasi & fungsi mencakup dua siklus dengan empat tahap yaitu: (1) perencanaan dengan menyusun dan memvalidasi RPP, lembar kerja siswa (LKS), lembar observasi aktivitas guru/siswa, serta tes akhir siklus, (2) pelaksanaan tindakan mencakup: a) kegiatan pendahuluan dengan menyampaikan tujuan pembelajaran, memberikan motivasi, penjelasan mengenai penggunaan mind map dan melakukan tanya jawab untuk menggali pengetahuan awal siswa mengenai materi sebelumnya serta materi yang akan dipelajari; b) kegiatan inti yakni membentuk siswa dalam kelompok kecil, memberikan LKS, siswa berdiskusi secara berkelompok, menuliskan hasil diskusinya pada LKS, membuat mind map terkait hasil diskusinya untuk presentasi di depan kelas, dan mempresentasikannya di depan kelas. Pada saat presentasi terjadi tanya jawab dan diskusi kelas terkait hasil presentasi; c) kegiatan penutup yakni guru mengevaluasi hasil diskusi kelas dan hasil mind map kelompok yang telah di presentasikan, (3) observasi dilakukan dengan tiga obsever, (4) refleksi terhadap hasil tes, mind map dan hasil observasi.Kata Kunci: Mind Map, Hasil Belajar, Relasi & Fungsi